Sacred and Space in Post-Secular Pilgrimage: The Camino de Santiago and Relational Model of the Sacred - Roszak, Piotr (The international journal of religious tourism and pilgrimage, 2019)
The aim of this paper is to shed light on the changes in perceiving the sacred which have appeared in the history of pilgrimage. These are linked with different theological approaches to space and subsequent periods of desacralisation, secularization and re-sacralisation. Relying on a modern theology of pilgrimage and research into the philosophy of religion by M. Eliade the paper offers a new interpretation of the message of the Camino de Santiago which overcomes previous reductionisms based on seeing the sacred solely in the destination (the shrine). The relationship with the Camino and the content of pilgrim blessings indicate the role of experiencing order, beauty and these virtues which shape the relational order (corresponding with the virtue of religio). The effort of pilgrims is linked to this, however, it is no longer described in terms of sacrifice' although it is related to the same content which is perceived in a new post-secular cultural context.